Assessment of Czech water-bodies ecological potential based on fish community - Blabolil, Petr (Jihočeská univerzita, 2017)
Ongoing environmental changes and increasing pressure on freshwater habitat require that we understand the ecological quality of freshwater ecosystems across a wide range of habitat types. This Ph.D. thesis addresses the utility of fish as ecological indicators in heterogeneous reservoir ecosystems. In the first section, I develop suitable indices and calculate ecological potential in two case studies, one using common fish guilds and traits at a large continental scale and another using species-specific indicators for a country-specific dataset. In the second section, I compare the assessment of fish communities across a large geographical region and identify anthropogenic stressors with the highest impact on fish communities. In the third section, I discuss the issue of optimal gillnet sampling design for reliable fish indicator values to increase the utility of assessment methodologies and to reduce sampling effort and fish mortality required to obtain reliable data. In the fourth section, I compare estimates of fish recruitment based on different sampling methods and develop a novel statistical approach to analyse factors affecting fish recruitment. This work provides an initial step towards the improvement of ecological quality of freshwater reservoirs.
Assessment of Czech water-bodies ecological potential based on fish community
Keywords: eutrophication; gillnet; indicator; reservoir; Water Framework Directive; eutrophication; gillnet; indicator; reservoir; Water Framework Directive